2018
DOI: 10.1037/fsh0000340
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder in Latin American families: Experiences in Chile.

Abstract: Results from this study highlight the importance of future research to better understand and treat Latin American children with ASD and their families. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The generation of public policies on early detection is necessary for the timely identification of each child with ASD, and it is essential that the treatment of children begin at an early age to achieve a significant impact on their evolution. A study conducted in Chile by Hartmann et al showed associations between ASD traits, physician support, community engagement, stigma, and family stress, highlighting “the importance of future research to better understand and treat Latin American children with ASD and their families” [51]. This study was an exploratory study carried out by a non-invasive sampling of the oral mucosa, which is a multi-stratified flat epithelial tissue that originates in the ectoderm, as does the nervous system [24].…”
Section: Discussionmentioning
confidence: 99%
“…The generation of public policies on early detection is necessary for the timely identification of each child with ASD, and it is essential that the treatment of children begin at an early age to achieve a significant impact on their evolution. A study conducted in Chile by Hartmann et al showed associations between ASD traits, physician support, community engagement, stigma, and family stress, highlighting “the importance of future research to better understand and treat Latin American children with ASD and their families” [51]. This study was an exploratory study carried out by a non-invasive sampling of the oral mucosa, which is a multi-stratified flat epithelial tissue that originates in the ectoderm, as does the nervous system [24].…”
Section: Discussionmentioning
confidence: 99%
“…The third quantitative study was conducted in Chile and explored the relationship between the severity of symptoms in children with ASD and other family characteristics, including stigma (Hartmann et al, 2018). With a study-specific questionnaire, the authors found stigma to be positively associated with ASD overall traits, social impairment, language and communication deficits, and family stress but not related to restricted and repetitive behaviors (RRBs).…”
Section: Attitudes and Beliefs About Id Perceived By Families And Carmentioning
confidence: 99%
“…Backtranslation of Western instruments is one way that global mental health researchers have tried to assure accurate measurement, but many other issues need additional study. Hartmann et al (2018) use previous work on measurement of caregiver distress done in the United States to develop an instrument for a survey in Chile, a country that has a higher income than LMICs. Based on findings from Chile, the authors suggest that the caregiver instrument could be used in other countries in Latin America because of shared culture.…”
Section: Obstacles To Obtaining Mental Health Servicesmentioning
confidence: 99%